Leukocytes Description of Mudskipper (Periophthalmodon schlosseri) of Barito River Estuary, Desa Tanipah, Kalimantan Selatan - Heri Budi Santoso; Hidayaturrahmah Hidayaturrahmah; Muhamat Muhamat (Biology, Medicine, & Natural Product Chemistry, 2018)
Leukocytes have an important role in driving away infections from pathogen microorganism by phagocytosis together with macrophages. The aim of this research was to analyze the leukocytes’ differentiation (eosinophil, basophil, neutrophil, lymphocytes, and monocytes) of mudskipper‘s blood (Periophthalmodon schlosseri). Samples were taken from desa Tanipah Kalimantan Selatan. The sampling locations were decided by purposive or taking the data intentionally according to the consideration of mudskipper‘s location which is not homogenous. The data collection were conducted using Line Transect which means the sample was taken according to how many encounters can be taken. There were 15 mudskippers taken from Desa Tanipah used in this research. The parameter observed wasthe differentiation of leukocytes which consists of the percentages of monocytes, lymphocytes, eosinophil, basophil, and heterophil. The result showed that the percentage of lymphocytes in mudskippers is 62+4,1%  and monocytes 24,7+0,8%, and the  neutrophil is 0,5+0,1% and eosinophil 0,6+0,1% and no basophils were found. According to the  result, it can be concluded that lymphocytesis the most dominant one amongst others.